How does the Niger river warm coastal waters in the northern Gulf of Guinea? - Topé, G. D. A.; Alory, G.; Djakouré, S.; Da-Allada, C.Y.; Jouanno, J.; Morvan, G. (Frontiers in Marine Science, 2023)
To highlight the processes by which the Niger River warms the coastal waters in the eastern part of the northern Gulf of Guinea upwelling, two simulations of the NEMO model at high resolution were used over the period 2010 - 2017. The first simulation is realistic while the second is a simulation in which the effects of the Niger River are not taken into account. The first step was to evaluate the outputs of the models, using satellite products and in situ observations. The average states of the Sea Surface Temperature, Salinity, Height, zonal current and vertical profiles of temperature and salinity showed the ability of the model to reproduce correctly the physical characteristics of the study area. The analysis of the heat balance terms of the two simulations showed that vertical diffusion and meridional advection processes are the causes of the warming induced by the Niger River. The stratification and vertical shear of the horizontal currents reveal that the river acts by inhibiting the upwelling of cold water induced by vertical diffusion. The river reinforces the stratification and prevents vertical shearing of horizontal currents at the bottom of the mixed layer.